Stability Analysis and Failure Mechanisms of Open Pit Rock Slope - Yahdi Azzuhry (Journal of the Civil Engineering Forum, 2016)
Rock mass in nature tend to be unideal, for it is heterogeneous, anisotropic and has discontinuity. The discontinuity makes anisotropic strength and stress in the rock mass, and also controls the changing of the elastic properties of rock mass. This condition results to disruptions in the rock mass strength balance, and finally drives the slopes to collapse. This study aims to determine the slope failure mechanisms in the area of case study, as well as its variations based on the Rock Mass Rating (RMR), Geological Strength Index (GSI), Slope Mass Rating (SMR), kinematic analysis, numerical analysis and monitoring approach slope movement in a coal mine slope applications. The site investigations were implemented to obtain information about slope collapse. Prior to the collapse, the slope inclination was 38° with of 94 meters height, strike slope of N 245 E and direction of slope surface of 335°. After the collapse, the slope was became 25º; and after the collapse materials were cleared, it was 35º. The discontinuity mapping obtained 5 sets of discontinuities, and the data were developed to obtain the value of RMR. The result of piezometer measurements was that at occurrence of collapse, slope elevation was 44.40m. Displacement value from monitoring SSMR showed that when the slope was collapsing in two stages, the first stage value was 70.61cm (a more critical condition, the value was rounded down to 70cm to the implementation in modelling) and the second stage value was at 124.25cm. The value of RMR89 in this study was greater than the value of GSI and SMR. As for the average value, it was obtained 34.67 for RMR89 value and 29.67 for GSI value, these rocks then can be classified into Poor Rock class number IV. The result of kinematic analysis found that sliding planar failure at dips 36°, and wedge failure at dips 36°, 35° and 34°. Acquisition SMR value obtained at 25, 27, 28 and 29. The SMR values classified the rock mass quality into class number IV, the description of the rock mass was relatively poor, the slope stability was low or unstable and the collapse manifold was planar or wedge failure. The result from the analysis of the model with its criteria obtained was that un-collapse conditions at angle 29°. It is recommended to use 29° angle to repair the slopes, and also recommended for overall high wall slope angle. Type of collapse that occurred on the slope failure mechanisms in all of the analysis that has been done, it is known that the mechanisms involved are complex types (combine of wedge failure, planar failure, and step-path failure) or classified into large scale rock slope failure surface.